Atopic eczema/atopic dermatitis - Ardern-Jones, Michael (Henry Stewart Talks, 2016)
Atopic eczema and eczema variants (epidemiology and impact of AE), Diagnostic criteria & clinical features, Complications of atopic eczema, Trigger factors, Allergic comorbidities, Pathophysiology, Current treatment, Future treatment